2022
DOI: 10.1108/bij-03-2022-0160
|View full text |Cite
|
Sign up to set email alerts
|

Examining the dark side of using gamification elements in online community engagement: an application of PLS-SEM and ANN modeling

Abstract: PurposeThe negative influence of gamification on online communities has received little attention in the available literature. The study examines the adverse effects of gamification during engaging in online communities.Design/methodology/approachGap-spotting methods were used to develop the research questions, followed by model development using the social exchange and social-network theories. Data were collected from 429 samples. The study applied partial least squares structural equation modeling to test th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 108 publications
0
1
0
Order By: Relevance
“…So, these keywords indicate that this cluster considers the study of factors affecting the intention to adopt gamified systems, that incorporate game elements, by customers [ 63 ]. Moreover, much of the research in this topic area uses partial least squares structural equation modelling analysis to test the model [ 64 , 65 ].
Fig.
…”
Section: Bibliometric Analysismentioning
confidence: 99%
“…So, these keywords indicate that this cluster considers the study of factors affecting the intention to adopt gamified systems, that incorporate game elements, by customers [ 63 ]. Moreover, much of the research in this topic area uses partial least squares structural equation modelling analysis to test the model [ 64 , 65 ].
Fig.
…”
Section: Bibliometric Analysismentioning
confidence: 99%
“…However, despite the presumed benefits of gamification, recent studies reveal conflicting findings regarding its effects on consumer behaviour. For example, Liu et al (2017) showed that the integration of gamification elements does not automatically yield positive results; other studies have reported that gamification leads to negative effects such as addiction, intolerance, mood swings (Srivastava et al , 2022), excessive participation (Hammedi et al , 2017), contradicting interactions (Leclercq et al , 2020) and even disengagement from the focal task (Leclercq et al , 2018). These particular effects have cast doubt on gamification’s efficiency and impelled scholars to set a supplemental research agenda that goes beyond the study of game elements.…”
Section: Introductionmentioning
confidence: 99%